Long-Term Outcome in Childhood-Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
The value of early seizure frequency and etiology in the prediction of long-term seizure and mortality outcome in a population-based cohort of 102 children was determined in a study at University of Turku, Finland, and Epilepsy Research Group, Berlin, Germany.